Typing of Burkholderia pseudomallei and association of its genotypes with clinical presentations and virulence - Harun, Azian (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Burkhoderia pseudomallei is a soil dwelling Gram-negative bacteria found mainly in the Southeast Asia region and northern Australia. Bacterial isolates from recent cases of melioidosis were collected and the genotypic diversity among these was explored using multi-locus sequence typing (MLST). Massive genotypic heterogeneity was observed among the 85 strains in which 23 different sequence profiles were observed. Sequence type 54 (ST54) was noted to predominate and two novel sequence types were discovered. Most of sequence types in this study were genetically related to each other and were clustered in a same group with those from Southeast Asian region and derived from the same ancestor which was ST 48. Analysis of association between the genotypes and clinical presentations explored the association of genotypes with predisposing factors, type of manifestation, severity of sepsis and mortality due to melioidosis. With regard to virulence association with genotypes, survival study and tissue burden analysis have been explored .